Impact of a randomized school-based intervention program on blood pressure levels - Raiani Spalenza Matos; Jordana Herzog Siqueira; Diana Barbosa Cunha; Maria del Carmen Bisi Molina (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to evaluate the impact of a health program performed in a school setting on the blood pressure levels of schoolchildren in the public school system in Vitória/ES-Brazil. Methods: a randomized community trial was performed with 237 schoolchildren (6 to 12 years) from two public schools, randomly defined as the intervention and control school. Participants of the intervention group attended 11 education sessions over 4 months (July to October 2014). To test for differences between groups, the chi-square (categorical variables), and the paired t test or Wilcoxon (continuous variables) was used. The rate of variation of systolic blood pressure (SBP) and diastolic blood pressure (DBP) throughout the follow-up, according to allocation group, was evaluated using linear generalized models for time-repeated measures. Results: there was a reduction in the means of SBP (0.5 mmHg) and DBP (0.6 mmHg) in the intervention group and an increase in the control group, with a significant difference in the BP variation between groups over the follow-up period (p<0.05). Conclusion: a low-cost and easily implemented intervention may be one of the factors associated with the lowest blood pressure levels in the group studied, and reproduction in a school environment is feasible.